2022
DOI: 10.1108/ijchm-04-2022-0440
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and gastronomy: a potential ‘marriage’? The case of Vietnam

Abstract: Purpose The purpose of this study is to gain a more nuanced understanding of the relationship between a national product (coffee) and gastronomy. Moreover, incorporating the resource-based view of the firm framework, the importance of coffee is examined, as is the extent and potential to “marry” coffee and gastronomy into a tourism activity, and the need to develop such potential. Design/methodology/approach Semi-structured, face-to-face and online interviews were used to gather the viewpoints of 79 chefs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…For example, Rahmanita (2019) through a study conducted in the Special Region of Yogyakarta, found that the Sekaten festival made a significant economic contribution to the Yogyakarta city economy through tourist spending. Similarly, a study conducted in Vietnam found that coffee and gastronomy have the potential to be "married" into tourism activities, which can have a positive impact on the local economy (Vu et al, 2022).…”
Section: Local Shoppingmentioning
confidence: 99%
“…For example, Rahmanita (2019) through a study conducted in the Special Region of Yogyakarta, found that the Sekaten festival made a significant economic contribution to the Yogyakarta city economy through tourist spending. Similarly, a study conducted in Vietnam found that coffee and gastronomy have the potential to be "married" into tourism activities, which can have a positive impact on the local economy (Vu et al, 2022).…”
Section: Local Shoppingmentioning
confidence: 99%
“…Buna istinaden kahve turizmiyle ilgili akademik ilginin arz odaklı konularda yoğunlaştığı ve çalışmaların sıklıkla paydaşlarla görüşme yapılarak sürdürüldüğü dikkat çekmektedir. Söz gelimi, konuyla ilgili arz odaklı birçok çalışma (Anbalagan & Lovelock, 2014;Degarege & Lovelock, 2021;Vu, Alonso, Martens, Do, Tran, Tran & Nguyen, 2023)…”
Section: Veri Toplama Süreciunclassified
“…Based on this, it is noteworthy that the academic interest in coffee tourism is focused on supply-oriented issues and the studies are frequently carried out by meeting with the stakeholders. Do, Tran, Tran, & Nguyen, 2023) show what the potential of coffee tourism is in destinations, how this type of tourism can be created. and it can be developed, and what kind of benefits coffee tourism can have for destinations within the scope of stakeholders.…”
Section: Extended Summarymentioning
confidence: 99%
See 1 more Smart Citation